Methane purification using PVC membrane : preparation, characterization and performance study - Raj Krishna Roshan, Kanasan (2017)
Methane gas is one of the most prevalent gaseous in the air yet it still has its benefits. Global methane emissions from landfill are estimated to be between 30 and 70 million tonnes each year. Most of this landfill methane currently comes from developed countries, where the levels of waste tend to be highest. A recent study was done at Kampung Sg. Ikan Landfill in Kuala Terengganu where the rubbish or wastes from the city of Kuala Terengganu was collected and the date were collected where wastes were segregated according to their 13 types, such as 3D plastic, 2D plastic, glass, and so on. In this study, a PVC membrane will be produced in order to separate CH4 gas from the CH4/CO2 mixture. The PVC membrane is produced by the combination of Polyvinyl Chloride (PVC) and N-Methyl-2-pyrrolidone, (NMP) via dry/wet phase inversion technique. The invention of this PVC membrane is expected to improve the characteristics of the polymeric membrane which is the permeability, selectivity and the pore size. PVC is introduced with ratio of NMP (solvent): PVC 82:18, 80:20, 77:23, and 75:25 in order to achieve the desired selectivity and permeability of CH4/CO2 gas separation. From the performance view, the PVC membrane with composition 77:23 are the most suitable to separate the two gases compared to the rest of the membranes respectively at 2 bars. This high-performance sample are proven by the SEM image of the surface morphology itself. The pore diameter range of 9.87μm – 28.7μm.